The (in)consistency of changes in brain macrostructure in male paedophiles: A combined T1-weighted and diffusion tensor imaging study. (September 2015) - Gerwinn, Hannah; Pohl, Alexander; Granert, Oliver; van Eimeren, Thilo; Wolff, Stephan; Jansen, Olav; Deuschl, Günther; Huchzermeier, Christian; Stirn, Aglaja; Siebner, Hartwig Roman; Ponseti, Jorge
Abstract: Thus far, four studies have used magnetic resonance imaging (MRI) to test for differences in brain structure between paedophilic (i.e. sexually attracted to pre-pubescent children) and teleiophilic (i.e. sexually attracted to adults) men, revealing divergent results. To re-examine this issue, we acquired high resolution structural T1-weighted and diffusion MRI scans of the brain in 24 paedophilic and 32 teleiophilic men. We performed voxel-based morphometry (VBM) of the T1-weighted images and tract-based spatial statistics (TBSS) of the diffusion tensor imaging data to search for grey and white matter differences between groups. In contrast to previous studies, less than half of the individuals in our paedophilic group had a record of sexual offences against children, as subjects were partially recruited from two outpatient facilities of a child sexual abuse prevention project for self-acknowledged paedophiles. After adjustment for multiple comparisons and controlling for important confounding factors, we did not find any significant grey or white matter differences between the paedophilic and teleiophilic subjects. Together with the inconsistencies in the literature, these results argue against consistent structural differences at the macroanatomical scale between paedophiles and teleiophiles. Graphical abstract: Highlights: We are the first to use the diffusion tensor imaging technique in paedophiles. We used an outpatient sample of paedophiles, controlling for age and education. We were not able to replicate findings of reduced grey matter in paedophiles. We were not able to find white matter differences between paedophiles and controls. Our null-finding adds to the rather inconsistent findings in the field of research.